Pengaruh Manajemen Pola Asuh Orang Tua Terhadap Kemandirian Belajar Siswa Kelas VI Madrasah Ibtidaiyah - Ubaidillah, Ubaidillah; Zuliani, Siti; Rozikin, Hari Khoirur; Solihin, Solihin (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyze the influence of parenting management on students' learning independence at the elementary school level. Using quantitative methods, this study involved 25 sixth grade students of MI Ma'arif Sidomukti Gresik and their parents. Data were collected through a questionnaire that measured parental parenting patterns, consisting of authoritarian, permissive, and authoritative aspects, as well as students' learning independence measured based on their ability to manage study time, complete assignments independently, and find learning resources. The results of the analysis showed that there was a significant relationship between parental parenting patterns and the level of students' learning independence. Authoritative parenting patterns were shown to have a greater positive impact compared to authoritarian and permissive parenting patterns. These findings indicate that the implementation of good parenting management by parents can contribute significantly to the development of students' learning independence. This study suggests that parents pay more attention to parenting approaches that support students' autonomy and responsibility in the learning process.